[tex]\frac{-1}{3}x[/tex] can be added to [tex]\frac{5}{6}x-4[/tex] to make it equivalent to [tex]\frac{1}{2}x-4[/tex].
Step-by-step explanation:
Let,
y be the term that can be added to given fraction.
Therefore;
[tex](\frac{5}{6}x-4)+y=\frac{1}{2}x-4[/tex]
Subtracting [tex]\frac{5}{6}x-4[/tex] from both sides to find y
[tex](\frac{5}{6}x-4)-(\frac{5}{6}x-4)+y=\frac{1}{2}x-4-(\frac{5}{6}x-4)\\\\\frac{5}{6}x-4-\frac{5}{6}x+4+y=\frac{1}{2}x+4-\frac{5}{6}x+4\\\\y=\frac{1}{2}x-\frac{5}{6}x\\\\y=\frac{3-5}{6}x\\\\y=\frac{-2}{6}x\\\\y=\frac{-1}{3}x[/tex]
[tex]\frac{-1}{3}x[/tex] can be added to [tex]\frac{5}{6}x-4[/tex] to make it equivalent to [tex]\frac{1}{2}x-4[/tex].
Keywords: fraction, subtraction
Learn more about fractions at:
#LearnwithBrainly